The Effect of Five E’s Learning Cycle Strategy in Teaching English Grammar on The Achievement of the Eighth Grade Students in Public Schools - Almaghreez, Alanood Sameer Fahed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to examine the effect of the five E’s learning cycle strategy in teaching English grammar on the achievement of the eighth grade students in the public schools.The study sample consisted of 90 students, (45 male and 45 female) Eighth grade students in Um Habibah School for Girls, and Wadi Al Seer School for boy during the first semester of the academic year 2017/2018.The study sample was distributed in to two groups: the first control group (23 males and 23 females) in which the students studied in the traditional way, the second group (22 males and 22 females) where students studied using the five E’s learning cycle strategy in teaching English grammar. The quasi - experimental approach was used to test the hypotheses of the study.The results indicated that there were statistically significant differences (α≤ 0.05) between the control and experimental groups in students, achievement of grammar for the eighth grade students in favor of the experimental group. And that there was statistically significant differences (α≤ 0.05) between the means of students who studied English grammar using the five E’s learning cycle strategy due to gender in favor of the females sample. The researcher recommends using the five E’s learning cycle strategy in teaching English grammar to students in the public schools and incorporating five E’s strategy in the English curriculum. It is also recommended that more research be conducted in the field of teaching English grammar, The researcher also recommends conducting more studies similar to the current study aimed at investigating the effectiveness of the five-year learning strategy, in acquiring scientific concepts and achievement in general.
Keywords: Effect of Five E’s Learning Cycle Strategy; Teaching English Grammar; The Achievement of the Eighth Grade Students